Lansia di era bonus demografi - Lilis Heri Mis Cicih; Darojad N. Agung (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
Currently, the demographic dividend era is in progress, but improving the quality of competitive human resources is still a challenging process. Human capital investment needs to be implemented to make the older person healthier, independent, prosperous and dignified in the future to reach the second demographic dividend. This study provides an overview of the older person and province characteristics in the era of the demographic bonus. The data sources are the 2019 National Socio-Economic Survey (Susenas) and other official publications. The analysis was carried out descriptively on a provincial scale for individuals aged 60 years or over. The results showed a dependency ratio below 50 (namely demographic bonus), but several provinces still needed to decrease fertility and mortality. Based on the older person's current condition, most still have low access to income, education, health services, and communication technology. Various efforts need to be implemented in collaboration between the government and other stakeholders to enhance the better quality of the older person in the next future. It is necessary to provide people with job opportunities, knowledge, and health and financial security skills to prepare for old age.